Microscopic investigations of Gold Basin and El Hammani chondrites - Szurgot, Marian; Polański, Krzysztof (Wydawnictwo Politechniki Łódzkiej, 2007)
Elemental and mineral composition of Gold Basin and El Hammami meteorites discovered in 1995 and 1997 have been studied by analytical electron microscopy and optical microscopy. It was established that the main meteorite minerals: olivines, pyroxenes, kamacite and taenite as well as troilite identified in the samples represent extraterrestrial minerals typical of the ordinary chondrites. Feldspars represented by plagioclase, orthoclase, magnetite, calcite, chromite and silica have been also present in the studied samples. Chemical and mineral composition, iron content, petrologic types of chondrules, their abundance and sizes, the presence of troilite veins and abundance of nonoxidised iron phases confirm H class of El Hammami chondrite, i.e.. olvine-bronzite class, and L class of Gold Basin, i.e. olivine-hyperstene class.

Badano skład chemiczny i mineralny meteorytów Gold Basin i El Hammami. Zanalizowano chondry i ciasto skalne. Obecność chondr oliwinowych, chondr piroksenowych, żył troilitowych oraz faz żelazo-niklowych: kamacytu i troilitu świadczą o pozaziemskim pochodzeniu badanych skał. Oprócz minerałów najbardziej rozpowszechnionych w meteorytach takich jak: oliwin, piroksen, kamacyt, taenit i troilit wykryto także plagiklazy, magnetyt, kalcyt, chromit, ortoklaz i krzemionkę. Zgodnie z uprzednią klasyfikacją Gold Basin jest chondrytem klasy L o niskiej zawartości żelaza, a El Hammami chondrytem typu H zawierającym dużo żelaza.
Badania mikroskopowe chondrytów Gold Basin i El Hammami